(untitled) (Journal of Universal Science Research, 2024)
The quality and beauty of clothes are the main requirements of fashion. Today, the art of weaving our Uzbek national fabrics and the production of natural silk fiber, which is a necessary raw material for these fabrics, is developing rapidly. "Performance" refers to the properties of fabrics such as air permeability, elongation and friction, durability, permeability, color fastness, shape retention